Results on Circular-Arc Bigraphs - Kolberg, Fabricio Schiavon; Groshaus, Marina; Guedes, André Luiz Pires; Carmo, Renato (Anais do Encontro de Teoria da Computação (ETC), 2016)
We present a series of results related to the structural properties of the bipartite graph class known as circular-arc bigraphs. We also propose the definition of a Helly circular-arc bigraph subclass, based on a concept known as bipartite-Helly, along with a few results related to its structural properties.